Talk radio and public debate : a case study of three Ugandan radio stations - Ogoso, Erich Opolot (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2005)
This study is a comparative examination of approaches to talk radio as a genre on three Ugandan radio stations. The aim is to draw conclusions, from observations made about these stations, about the potential of talk radio to encourage public debate around social issues and improve democratic participation despite pertinent challenges in Uganda. The study first outlines a theoretical framework, which is informed by Habermas's theory of the media as a 'public sphere'. This framework is applied to an exploration of traditions of talk radio that have emerged globally in order to assess the potential of these traditions to play a role in contributing to the establishment of such a 'public sphere'. The study then goes on to discuss the historical development of radio in Uganda and the establishment of the current broadcast landscape. The focus is on the way in which this history has been defined by a struggle around public expression, in which government has repeatedly sought ways to control media as a vehicle for public expression. It is proposed that Ugandan talk radio has the potential to play an important role in ensuring broad participation in public expression. It is against this background that the study then describes and analyses the development of the talk genre at three Ugandan radio stations (each one an example of, respectively, a commercial, community and public service station). It is explained that staff on all three stations emphasise the importance of talk radio in encouraging participation, by their audiences, in the public debate of social and political issues. It is argued that, because of limitations that exist within these stations, none of the talk show teams fully realize the potential of the genre for participation in such debate. The picture that emerges is one of unequal access, with those sections of radio audiences in positions of privilege being further empowered, while those on the margins remain excluded from public discussion. The study finally recommends ways to improve public participation on Ugandan talk radio, noting the need to review government support, the problems of organizational culture within the stations, the need for more guidelines on practical arrangements around talk show production and the question of contradictions that exist at policy level.
Keywords: Radio stations -- Uganda; Radio broadcasting -- Social aspects -- Uganda; Radio broadcasting -- Political aspects -- Uganda; Radio talk shows -- Uganda; Interviewing on radio -- Uganda